THE USE OF MULTIMEDIA INTERACTIVE ONLINE GAMIFICATION ELEMENTS IN EDUCATION (International journal of artificial intelligence, 2026)
This paper explores the use of multimedia interactive online gamification elements in education and their impact on learner motivation, engagement, and academic performance. Through a systematic review of empirical studies and theoretical frameworks, the research highlights how gamified multimedia tools—such as points, badges, leaderboards, and interactive content—enhance cognitive processing and support self-regulated learning. Statistical evidence demonstrates significant improvements in course completion rates, knowledge retention, and overall learner satisfaction. The study also discusses the importance of aligning gamification strategies with pedagogical objectives and addressing technological and cultural factors. The findings suggest that multimedia interactive gamification is a promising approach to enriching digital education and improving learner outcomes.